Auto-regulation of the thyroid gland beyond classical pathways - Brix, Klaudia; Szumska, Joanna (Experimental and clinical endocrinology & diabetes, 2020)
This mini-review asks how self-regulation of the thyroid gland is realized at the cellular and molecular levels by canonical and non-canonical means. Canonical pathways of thyroid regulation comprise thyroid stimulating hormone-triggered receptor signaling. As part of non-canonical regulation, we hypothesized an interplay between protease-mediated thyroglobulin processing and thyroid hormone release into the circulation by means of thyroid hormone transporters like Mct8. We proposed a sensing mechanism by different thyroid hormone transporters, present in specific subcellular locations of thyroid epithelial cells, selectively monitoring individual steps of thyroglobulin processing, and thus, the cellular thyroid hormone status. Indeed, we found that proteases and thyroid hormone transporters are functionally inter-connected, however, in a counter-intuitive manner fostering self-thyrotoxicity in particular in Mct8- and/or Mct10-deficient mice. Furthermore, the possible role of the G protein-coupled receptor Taar1 is discussed, because we detected Taar1 at cilia of the apical plasma membrane of thyrocytes in vitro and in situ. Eventually, through pheno-typing Taar1-deficient mice, we identified a co-regulatory role of Taar1 and the thyroid stimulating hormone receptors. Recently, we showed that inhibition of thyroglobulin-processing enzymes results in disappearance of cilia from the apical pole of thyrocytes, while Taar1 is re-located to the endoplasmic reticulum. This pathway features a connection between thyrotropin-stimulated secretion of proteases into the thyroid follicle lumen and substrate-mediated self-assisted control of initially peri-cellular thyroglobulin processing, before its reinternalization by endocytosis, followed by extensive endo-lysosomal liberation of thyroid hormones, which are then released from thyroid follicles by means of thyroid hormone transporters.
Gesehen am 28.07.2020